An umbrella review of systematic reviews and meta-analysis of risperidone on cardiovascular risk: analysis of 11,949 patients - Gianini, Silvia Helena Soares [UNESP]; Grecca, Igor Soares Gianini [UNESP]; Folegatti, Derfel Rodrigo Maciel Alba [UNESP]; Oliveira, Camila Marcondes de [UNESP]; Raimundo, Rodrigo Daminello [UNESP]; Porto, Andrey Alves [UNESP]; Valenti, Vitor Engrácia [UNESP] (Elsevier, 2025)
Background A new Systematic Review (SR) suggested that antipsychotic drugs are involved with cardiometabolic problems. To better understand this issue, we conducted an Overview of SRs to evaluate the effects of risperidone on cardiovascular risk. Objectives To verify if there is any cardiovascular risk in people who are treated with Risperidone. Methods The searches were completed by means of EMBASE, MEDLINE/PubMed (by National Library of Medicine), Scopus, and Web of Science databases. We included SRs of risperidone and cardiovascular risk published up until 2022. PRISMA was enforced for reporting quality, AMSTAR 2 was necessary for methodological quality and GRADE was executed for quality of evidence analysis. Results After excluding 1883 publications, we designated six SR, that did not detect substantial effects of risperidone on tachycardia events ((relative effect: 1.35 (0.87, 2.1)), systolic blood pressure ((absolute effect: 1.07 (1.12, 3.26)) and diastolic blood pressure (absolute effect: 1.35 (1.48, 4.18)), QTC prolongation events ((relative effect: 1.02 (0.94, 1.1)) and QTC prolongation ((absolute effect: 9.39 (4.09, 14.69)). No SR entirely adhered to the PRISMA statement, AMSTAR 2 and GRADE suggested low to very low quality. Conclusion The SRs demonstrated no significant impact of risperidone on cardiovascular risk. Yet, we advise improvement in the evidence, methodological and reporting quality for impending SRs. Implications The current evidence did not report substantial cardiovascular adverse effects about risperidone treatment, backing up its cardiovascular safety. Nevertheless, the low to very-low methodological quality and low to very-low quality of evidence highlight the requirement for stronger and more robust evidence based on further scientific research.